Is the primary visual cortex necessary for blindsight-like behavior? Review of transcranial magnetic stimulation studies in neurologically healthy individuals - Railo Henry; Hurme Mikko (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The visual pathways that bypass the primary visual cortex (V1) are often assumed to support visually guided behavior in humans in the absence of conscious vision. This conclusion is largely based on findings on patients: V1 lesions cause blindness but sometimes leave some visually guided behaviors intact-this is known as blindsight. With the aim of examining how well the findings on blindsight patients generalize to neurologically healthy individuals, we review studies which have tried to uncover transcranial magnetic stimulation (TMS) induced blindsight. In general, these studies have failed to demonstrate a completely unconscious blindsight-like capacity in neurologically healthy individuals. A possible exception to this is TMS-induced blindsight of stimulus presence or location. Because blindsight in patients is often associated with some form of introspective access to the visual stimulus, and blindsight may be associated with neural reorganization, we suggest that rather than revealing a dissociation between visually guided behavior and conscious seeing, blindsight may reflect preservation or partial recovery of conscious visual perception after the lesion.